Modification of a Thermoplastic Polyurethane Surface for Creating a Soft Robotic Gripper Using a Four-Dimensional Printing Method - Zakharova, Vasilina A.; Mikailov, Raul G.; Saryglar, Roza Yu; Lagunov, Vladislav S.; Baranov, Oleg V.; Kovaleva, Polina A.; Peshkina, Elizaveta A.; Ivantsova, Ekatherina A.; Permyakova, Elizaveta S.; Koudan, Elizaveta V.; Senatov, Fedor F. (ACS applied engineering materials, 2025)
One of the avenues for the development of functional gradient additive manufacturing is the creation of four-dimensional (4D) printed structures for soft robotic gripping, achieved by combining fused deposition modeling 3D printing with soft hydrogel actuators. This work proposes a conceptual approach to creating an energy-independent soft robotic gripper, consisting of a modified 3D printed holder substrate made from thermoplastic polyurethane (TPU) and an actuator based on a gelatin hydrogel, allowing programmed hygroscopic deformation without using complex mechanical constructions. The use of a 20% gelatin-based hydrogel imparts soft robotic biomimetic functionality to the structure and is responsible for the intelligent stimulus-responsive mechanical functionality of the printed object by responding to swelling processes in liquid environments. The targeted surface functionalization of thermoplastic polyurethane in an argon–oxygen environment for 90 s, at a power of 100 W and a pressure of 26.7 Pa, facilitates changes in its microrelief, thus improving the adhesion and stability of the swollen gelatin on its surface. In this work, the morphological (scanning electron microscopy and atomic force microscopy), colloidal, chemical (FTIR), physicochemical (swelling), biological (cell biocompatibility), and performance evaluations of the TPU/gelatin gripper were studied. The realized concept of creating 4D printed biocompatible comb structures for macroscopic underwater soft robotic gripping can provide noninvasive local gripping, transport small objects, and release bioactive substances upon swelling in water. The resulting product can therefore be used as a self-powered biomimetic actuator, an encapsulation system, or soft robotics.